SOME ASPECTS OF USING INFORMATION TECHNOLOGIES FOR TEACHING FOREIGN LANGUAGES IN HIGHER SCHOOL - Ponikarovska, S.; Поникаровская, С. В.; Понікаровська, С. В. (Харьковский национальный автомобильно-дорожный университет, 2017)
The article deals with the peculiarities of using information technologies in the process of teaching foreign languages in higher school. The positive and negative features have been determined and a number of reasons for insufficient or simplified usage of electronic means of education have been given.
НЕКОТОРЫЕ АСПЕКТЫ ИСПОЛЬЗОВАНИЯ ИНФОРМАЦИОННЫХ ТЕХНОЛОГИЙ В ОБУЧЕНИИ ИНОСТРАННЫМ ЯЗЫКАМ В ВЫСШЕЙ ШКОЛЕ
ДЕЯКІ АСПЕКТИ ВИКОРИСТАННЯ ІНФОРМАЦІЙНИХ ТЕХНОЛОГІЙ У НАВЧАННІ ІНОЗЕМНИХ МОВ У ВИЩІЙ ШКОЛІ
Keywords: environment; visual; content; skills; perception; среда; визуальный; контент; навыки; восприятие; середовище; контент; навички; візуальний; навички; сприйняття; 378.147